Three Settings in Seneca’s Phaedra - Rzepkowski, Krzysztof (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2017)
In the following article I present my own concept for interpreting Seneca’s Phaedra, demonstrating that the action takes place in three distinct settings: that of the royal palace (DOMUS), which is the domain of Phaedra’s actions, that of the city of Athens (URBS), which is the realm of Theseus and the Nurse, and that of the forest (SILVAE), which constitutes the world of Hippolytus. In the second part of the article I propose to arrange the stage in a way that takes the proposed settings into account.